Administering fiscal regimes for extractive industries a handbook - Calder, Jack, 1948- (Washington, D. C. International Monetary Fund, 2014)
This handbook is one of the first of its kind to focus attention on effectively administering revenues from extractive industries. It provides policymakers and officials in developing and emerging market economies with practical guidelines to establish a robust legal framework, organization, and procedures for administering revenue from these industries. It discusses transparency and how to promote it in the face of increasing demands for clarity and how developing countries can strengthen their managerial and technical capacity to administer these revenues.
Contents: What's special about natural resource revenue administration? - - Policy and legal framework - - Organization and cooperation - - Procedures - - Governance and transparency - - Administrative capacity.
Includes bibliographical references and index.
Keywords: Mineral industries -- Taxation -- Handbooks, manuals, etc; Natural resources -- Taxation -- Handbooks, manuals, etc; Revenue -- Accounting -- Handbooks, manuals, etc; Tax administration and procedure -- Handbooks, manuals, etc